The Diversity of Pest Generalist Predator in Potato Plants (Solanum tuberosum L.) Treated By Non-Synthetic Chemistry Insecticide on The Medium Plain of Lombok Island - Muhammad Sarjan; Sudirman Wahyu Astiko; Citra Sintia Andari; Baiq Minarti Rismanovi (Journal of Science and Science Education, 2020)
This study aims to determine the diversity, abundance, and dominance of predators in potato plants treated by synthetic non-chemical insecticides on the medium plain of Lombok Island. The research used Randomized Block Design with ten different synthetic non-chemical insecticide treatments such as Metarhizium anisopliae, Beauveria bassiana, and Bacillus thuringiensis, Neem extract, tobacco stem extract, soursop leaf extract, babandotan leaf extract, chemical insecticide treatment, and one treatment without insecticide as a control. The insecticide was applied after 37 days of planting eight times at 7-day intervals. The type and population of predators were observed five days after the treatments. The diversity index (H'), abundance (K), and dominance (D) of the predators are then identified and determined. Data were analyzed by using a Diversity analysis followed by a 5% beda nyata jujur (BNJ). The yield shows six predatory families: Formicidae, Coccinellidae, Mantidae, Lycosidae, Oxyopidae, and Aranedae. H' and K values are generally classified as the low category, and no species dominates in each treatment (D <0.5). The value of H' and K in B. thuringiensis treatment was higher than other treatments. The highest D value was obtained from chemical insecticide treatment. Formicidae is the family with the highest population compared to other families